Street food traders, farmers and sustainable practice to reduce food waste in the Italian context - Alfiero, Simona; Christofi, Michael; Bonadonna, Alessandro (My University, 2020)
Purpose: The purpose of this paper is to demonstrate how food waste management can affect both retail and distribution operators’ efficiency performance and their ability to create value. In particular, the paper shows how optimizing food waste management characterizes best practices and favors the development of sustainability. Design/methodology/approach: Based on a survey of 196 outdoor market operators (including farmers and street food traders) from 27 outdoor markets, the authors analyzed unsold food/food wastage processes vis-à-vis the operators’ behavior and attitude. To provide accurate definitions of the satisfaction levels, a consumer perception survey was carried out, with a usable sample of 2,107 questionnaires. The efficiency performance was evaluated according to data envelopment analysis. Findings: The results showed that farmers operate more efficiently than street food traders and that the traditional management of unsold food/food waste is an important competitive element in this sector. Research limitations/implications: The sample represents the Greater Turin Area in Italy, i.e., thus, limiting generalizability of the results. In addition, the variables analyzed were limited to certain aspects of selling processes and food waste management. Practical implications: The results provide some indicators on how a more rational style of unsold food management can improve an operators’ performance and help make a social impact. Originality/value: To the best of the authors’ knowledge, this is the first study that analyses outdoor market operators’ efficiency, based on the use of food waste as a variable affecting their performance.
Keywords: Data envelopment analysis; Farmers; Food waste; Outdoor market; Street food traders; Unsold food